Sources of labour growth in Malaysian manufacturing sector - Poo, Bee Tin; Abdul Rashid, Zakariah; Mohd Noor, Zaleha; Law, Siong Hook (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2011)
Manufacturing sector play an important role in the Malaysian industrial development. High growth rates and technology expansion in the manufacturing sector resulted in a substantial increase in demand for labour. This process of rapid growth and changes in labour were also accompanied by changes in labour structure and skills. At the same time, the range of activities and products became more diversified and correspondingly sub sectors composition of manpower changed significantly. This study employed the input-output SDA. The analysis computed the compositional manpower change as a result of decomposition. The result of this study indicates that sources of labour growth in the manufacturing sector were favored by changes in the final demand structure. Within the changes in the final demand structure, changes in domestic demand structure were the dominant source of employment growth during 1978-1991 and overall period 1978-2000. However, from 1991 to 2000, an employment change was due mainly to changes in export structure. Changes in the structure of domestic demand had relatively strong increasing effect on service workers, production and related workers, transport equipment operators and laboures and clerical and related workers during 1978-1991. Changes in the export structure were the main factor that had an employment increasing effect on high skill workers and sales workers. However, during the second sub period 1991-2000, manpower growth was exports structure driven. Interestingly, human capital accumulation occurred in the heavy industry was higher than light industry over the period considered.